High School and College Choice Factors Associated with High-Achieving Low-Income Students' College Degree Completion - Adriana Ruiz Alvarado; Theresa Stewart-Ambo; Sylvia Hurtado (MDPI AG, 2020)
Gaps in college degree completion between low-, middle-, and high-income college students are typically attributed to differences in academic preparation and ability. However, high-achieving, low-income students are still less likely to graduate from college than their high-achieving, high-income counterparts. This study explores completion rates at the end of the Great Recession, using a community cultural wealth framework to examine additional pre-college factors and college attendance behaviors that contribute to the degree completion of high-achieving, low-income students. Longitudinal data using the Freshmen Survey and National Student Clearinghouse were collected from 2004 to 2010, comparing 9300 high-achieving students entering 455 colleges from low-, middle-, and high-income backgrounds. Hierarchical linear modeling (HGLM) was used to identify student and institutional factors that predict college completion during this era. Findings indicate that navigational capital and college attendance patterns (attending a summer session, selective college, and/or private institution) are key factors for high-achieving, low-income student completion. Cultural wealth anti-deficit measures could not explain the low-income Latinx lower likelihood of college completion nor gender differences across income groups. Implications of the results address concerns regarding the COVID-19 pandemic recession in terms of what institutions can do to support students.